Distractor rejection in parallel search tasks takes time but does not benefit from context repetition. - Ng, Gavin Jun Peng; Buetti, Simona; Dolcos, Sanda; Dolcos, Florin; Lleras, Alejandro (Visual Cognition)
When the spatial configuration of a search display is presented repeatedly, response times to finding the target within that configuration are shorter compared to completely novel configurations, even though observers do not have explicit recognition of the repetition. This phenomenon is known as Contextual Cueing and selective attention is thought to be necessary for the effect. Previous research has suggested that repetition of the context of unattended items does not appear to improve performance; only repetition of attended items does. It has been proposed that this occurs because unattended items are pre-attentively filtered and thus do not contribute to performance. Here we demonstrate that so-called "unattended" items do contribute to performance, just not to contextual cueing. We approach this question from the perspective of the parallel processing of the scene that unfolds at the start of each item and that has been recently modelled by the Target Contrast Signal Theory. We show that the processing time per item during parallel evaluation of the scene is not affected by context repetition, suggesting that the locations of the items rejected in this stage are not integrated into the memory representation underlying contextual cueing. Other alternatives are also discussed.